Adherence to the post-exposure prophylaxis among animal bite patients attending rabies clinic at tertiary care hospital – A cross-sectional study - Shivasharan HN,; Chaitra Ramesh Chavan,; Neeta PN,; Sameena ARB,; Suresh CM,; Ramesh K,; Ananthachari KR, (Asian Journal of Medical Sciences, 2024)
Background: Rabies is an acute and 100% fatal viral disease transmitted to humans through the bite or lick of an infected animal. It can be successfully prevented if a complete course of anti-rabies vaccine (ARV) is taken following an animal bite. The present study reveals the compliance of animal bite victims to post-exposure prophylaxis (PEP). Aims and Objectives: The objectives of the study are as follows:(1) To determine the adherence to PEP among animal bite victims and factors influencing it. Materials and Methods: A retrospective record-based cross-sectional study was conducted at the anti-rabies clinic of VIMS Hospital Ballari. Information regarding sociodemographic variables, animal bite history, category of bite, treatment received, and completion of ARV schedule of all the animal bite cases were collected from the animal bite register and treatment card during the period from July 2023 to December 2023. Results: Out of the total 350 animal bite victims, all of them received the first dose of vaccine, 86.28% completed two doses, 72% completed three doses, and only 51.14% completed the schedule by taking all four doses, 37% of them completed the schedule without any delay, 14% delayed one or more doses, and the rest 49% did not complete the schedule. Conclusion: Adherence to PEP is a dire necessity as rabies is a fatal disease. Counseling the animal bite victims about the importance of adhering to the complete PEP schedule at the time of administering the first dose of vaccine is crucial.